2022
DOI: 10.15585/mmwr.mm7133a4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outbreaks and Mortality Among Public Transportation Workers — California, January 2020–May 2022

Abstract: Work-related factors can contribute to risk for exposure to and infection with SARS-CoV-2, the virus that causes COVID-19, and subsequent COVID-19-attributable outcomes, including death. Comparing COVID-19 metrics across industries can help identify workers at highest risk. Elevated COVID-19 mortality rates have been reported among all transportation workers, as well as specifically in public transportation industries (1-3). The California Department of Public Health (CDPH) calculated public transportation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…High prevalence of COVID-19 infection was also found in bus drivers in Madrid, Spain between 25 March and 11 July 2020 through a screening program for essential workers ( Martínez-Cortés et al, 2022 ). In California, COVID-19 outbreak incidence during January 2020–May 2022 was 5.2 times as high in the bus and urban transit industry as in other industries in the state ( Heinzerling et al, 2022 ). This strengthens the indications of an occupational risk for SARS-CoV-2 infection among bus drivers.…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of COVID-19 infection was also found in bus drivers in Madrid, Spain between 25 March and 11 July 2020 through a screening program for essential workers ( Martínez-Cortés et al, 2022 ). In California, COVID-19 outbreak incidence during January 2020–May 2022 was 5.2 times as high in the bus and urban transit industry as in other industries in the state ( Heinzerling et al, 2022 ). This strengthens the indications of an occupational risk for SARS-CoV-2 infection among bus drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Large outbreaks in meat-packing plants, nursing homes, and prisons made it evident early in the pandemic that certain work settings imposed an elevated risk of SARS-CoV-2 exposure. [18][19][20][21] Additional evidence, established through outbreak investigations and epidemiologic studies, have further demonstrated the role of work in generating disparities in COVID-19 illness, morbidity, and mortality by industry and occupation [22][23][24][25][26][27][28][29][30][31][32] above and beyond socio-environmental factors. 33,34 Second, the specific source of a person's COVID-19 illness is often difficult if not impossible to identify.…”
Section: Rationale For a Covid-19 Presumptionmentioning
confidence: 99%
“…Public transport passengers [ 28 , 29 ] and workers [ 30 , 31 ] are the most-at-risk populations of contamination due to: (1) a high passenger flow density; (2) forced contact with a large number of often infected people who arrive from regions where mass vaccination has not yet been carried out; (3) the mixing of the populations of different districts of the city and different cities and countries; (4) difficulty in maintaining social distance; (5) a low social responsibility of people with symptoms of the disease using public transport. Thus, according to Heinzerling A. et al, the incidence of COVID-19 among workers in the transport industry was 5.2 times higher in the bus and urban transport industries and 3.6 times higher in the air transport industry than in all California industries combined [ 32 ]. Therefore, wearing personal equipment that reduces the risk of spreading COVID-19 on public transport by both passengers and workers is especially important.…”
Section: Introductionmentioning
confidence: 99%